The Influence Of Competence And Work Training On Employee Performance With Work Effectiveness As A Mediating Variable At Pt. Unicorn Tosan Perkasa - Asep Mulyadi; Nurul Hermina (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyze the effect of competence and training on employee performance with work effectiveness as a mediating variable at PT Unicorn Tosan Perkasa. Amid increasing business competition, companies must ensure that employees have adequate competencies and undergo effective training to achieve optimal performance. Despite various efforts in human resource development, employee performance has not fully met the expected targets. Therefore, this study examines how competence and training influence employee performance and the role of work effectiveness as a mediating variable. The method used is Structural Equation Modeling (SEM) to test the relationships between variables. The results show that competence significantly affects work effectiveness and employee performance, as does training. Work effectiveness mediates the influence of competence and training on employee performance. In conclusion, the company needs to enhance employee competence and training to improve overall performance and work effectiveness.